Use suitable identities to find the products of the following expressions. (a.) (x-6)²
Answers
Answered by
1
Answer:
use formula and u will get the answer
Step-by-step explanation:
(a-b)^2
Answered by
0
Answer:
Step-by-step explanation:
use identity (a -b )^2
(x-6)square= using property (a-b)square
=xsquare-2*6*x + 6square=asquare-2ab+bsquare
final answer =xsquare-12x +36
Similar questions
Science,
3 months ago
Environmental Sciences,
3 months ago
English,
3 months ago
Math,
7 months ago
Business Studies,
1 year ago
Math,
1 year ago